Cover Image, Volume 29, Issue 8. (August 2016) - Lau, Justin Y. C.; Chen, Albert P.; Gu, Yi‐Ping; Cunningham, Charles H.
Abstract : The cover image, by Justin Y. C. Lau et al., is based on the Research Article Voxel‐by‐voxel correlations of perfusion, substrate, and metabolite signals in dynamic hyperpolarized 13 C imaging, DOI:10.1002/nbm.3564 .